1‐year outcome after treatment of uterovaginal prolapse with a 6‐point fixation mesh. Issue 4 (14th March 2019) - Brandt, Andreas; Kuszka, Andrzej; Niesel, Achim; Lutz, Henrik; Fünfgeld, Christian; Mengel, Mathias; Ulrich, Daniela
Abstract: Introduction: The aim of this study was to describe the safety and anatomical results of a surgical approach with a single‐incision 6‐point fixation vaginal mesh for the treatment of pelvic organ prolapse at perioperatively and at 1‐year follow‐up. Materials and Methods: This was a prospective observational study of patients who underwent operation receiving an InGYNious anterior transvaginal mesh. All patients with symptomatic stage II prolapse or higher were included in the study. Exclusion criteria were the unwillingness or inability to give written informed consent, neuromuscular disorders, malignant diseases, previous radiation in the pelvis, or chronic pain syndrome. Every patient completed a structured questionnaire and a full physical examination according to the IUGA‐ICS POP‐Q staging system before the operation and at 1‐year follow‐up. Results: Two hundred fifty‐four patients (91%) were included in the study. The intraoperative complication rate was 7% with hemorrhage being the most common complication. Six patients (2.4%) had undergone reoperation for prolapse (four out of the six patients had reoperation in the posterior compartment) and were excluded from the objective outcome analysis. In the remaining 248 patients all POP‐Q measurements were significantly improved in the anterior and apical compartments. Similarly, urge urinary incontinence and voiding dysfunction improved significantly. Conclusions: In this series, the objective outcome one year after the InGYNious mesh was good with low numbers of mesh‐related problems or reoperation for prolapse.